New constraints on Ti diffusion in quartz and the priming of silicic volcanic eruptions - Audétat, Andreas; Schmitt, Axel Karl; Njul, Raphael; Saalfeld, Megan; Borisova, Anastassia; Lu, Yongjun (Nature Communications, 2023)
Titanium diffusion profiles in quartz crystals are widely applied to constrain the duration of magmatic processes. However, experimentally determined Ti diffusion coefficients in quartz diverge by three orders of magnitude. To rectify this problem we derive Ti diffusion coefficients from natural quartz phenocrysts from the 1991 eruption at Mt. Pinatubo, by combining U-Th ages of small (15-40 µm long) zircon inclusions with Ti diffusion profiles measured at nearby growth zone contacts in the same quartz crystals. Application of the obtained data to quartz crystals with Ti-rich rims from thirteen silicic volcanic tuffs worldwide suggests that the magmas erupted years to thousands of years after magma chamber rejuvenation, with the priming time increasing with magma volume and decreasing temperature. Here we show that the time scales involved in the generation of silicic volcanic eruptions are much longer than originally thought.